RESPON INDONESIA TERHADAP KEBIJAKAN PROTEKSIONISME EKONOMI NIGERIA TAHUN 2012-2016 - Niki Adea Putri; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describe the respons of Indonesia toward the economic protectionisme policy of Nigeria in 2012-2016. Nigeria are one of states in Africa Regions that have a big populations and a potency in oil and mineral. As a states that have a big potency in oil and mineral so Nigeria have a big impor then export in order that since 2004 the Government of Nigeria have done implemented the economic protectionisme policy likes import prohibit policy, tariff porduct policy and standarizations product. Thats policy have impact for export product from Indonesia because nigeria are one of market potention Indonesia from export non oil mineral product.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the respons of Indonesia toward the economic protectionisme policy of Nigeria. The theories applied in this research are merchantilism with the nations state analyze and national interest concept, the foregin policy theory.The research have conclusions that the respons of Indonesia toward the economic protectionisme policy of Nigeria are by somes step policy likes Government of Indonesia have a create Indonesia Trade Promotions Centre (ITPC) in Lagos Nigeria as a tade missions by Trade Agency, The Government of Indonesia and Nigeria have a dealling about Preferential Trade Agreement (PTA) and the Government of Indonesia create a international bussiness exhibitions in Nigeria and Tunisia for market brief in Nigeria.Key words: respons, economics, protectionime and policy